Effects of Interpersonal Communication and Compensation on Employee Performance of PT Panen Jaya Sepasang Palembang - Richo Mahendra; Luis Marnisah; Muhammad Wadud (International Journal of Marketing & Human Resource Research, 2022)
This study aims to investigate the effects of interpersonal communication and compensation on the performance of employees of PT Panen Jaya Sepasang Palembang. A sample of 90 respondents were obtained using a non-probability sampling technique. Data were collected through questionnaires and observations, and analyzed employing the multiple linear regression method. The results evince that partially each interpersonal communication and compensation has a significant effect on employee performance. Likewise, simultaneously, interpersonal communication and compensation have a significant effect on employee performance. This research is beneficial for PT Panen Jaya Sepasang Palembang. To improve employee performance, the company must pay attention to interpersonal communication and compensation factors.